Genome sequence of three Psychrobacter sp. strains with potential applications in bioremediation - Lasa, Aide (Genom Data, 2017)
To date, the genus Psychrobacter consists of 37 recognized species isolated from different sources, however they are more frequently found in cold and other non-polar environments of low water activity. Some strains belonging to the genus have shown different enzymatic activities with potential applications in bioremediation or food industry. In the present study, the whole genome sequences of three Psychrobacter-like strains (C 20.9, Cmf 22.2 and Rd 27.2) isolated from reared clams in Galicia (Spain) are described. The sequenced genomes resulted in an assembly size of 3,143,782 bp for C 20.9 isolate, 3,168,467 bp for Cmf 22.2 isolate and 3,028,386 bp for Rd 27.2 isolate. Among the identified coding sequences of the genomes, mercury detoxification and biogeochemistry genes were found, as well as genes related to heavy metals and antibiotic resistance. Also virulence-related features were identified such as the siderophore vibrioferrin or an aerobactin-like siderophore. The phylogenetic analysis of the 16S rRNA gene suggested that these strains may represent novel species of the Psychrobacter genus. The genome sequences of the Psychrobacter sp. strains have been deposited at DDBJ/EMBL/GenBank under the accession numbers MRYA00000000 (Cmf 22.2), MRYB00000000 (Rd 27.2) and MRYC00000000 (C 20.9), and the sequences could be found at the site https://www.ncbi.nlm.nih.gov/bioproject/PRJNA353858.